CONTRACTURA EN ADUCCION DE CADERA EN PARALISIS CEREBRAL. TRATAMIENTO QUIRURGICO - Benavente Arce, Fernando (2024)
In cerebral palsy there is an imbalance of muscle power in the hips, that cause adduction deformity followed by flexion and Internal rotation. lf the imbalance is marked and if the faulty postural habits are allowed to continue, adaptative changes develop in the soft tissue and bones increasing the anteversion and valgus of the femoral neck and thc hip may eventually subluxnte or dislocate. In patients with cerebral palsy we realized 302 surgical procedures in hip. In this work we evaluate 46 patients with 92 hips operated wlth adductor tenotomy, gracilis tenotomy and or anterior branch obturator neurectomy, continuing wlth active and passive exercise of the hips and knees. In nonambulators patients the nursing care were improved in 9S per cent of hips, and in ambulators the gait lmproved in 92 per cent; and the index of migration in 70 per cent.